Evidence-based implant dentistry and systemic conditions - Javed, Fawad, 1976-; Romanos, Georgios (Hoboken, NJ : John Wiley & Sons, Inc., 2018)
'This book provides essential information on the osseointegration and survival of dental implants in medically challenged patients'--Provided by publisher.
Evidence-based grading of studies -- Dental implants in patients with autism spectrum disorders -- Dental implants in patients with cardiovascular disorders -- Dental implants in patients with Crohn's disease -- Dental implants in patients with eating disorders -- Dental implants in patients with epilepsy -- Dental implants in patients with hepatic disorders -- Dental implants in patients with diabetes mellitus -- Impact of oral cancer therapy on the survival of dental implants -- Oral cancer arising around dental implants -- Dental implants in patients with periodontitis -- Success and survival of dental implants during pregnancy -- Dental implants in patients with psychological/psychiatric disorders -- Dental implants in patients using recreational drugs -- Dental implants in patients with renal disorders -- Dental implants in patients with rheumatic diseases -- Dental implants in patients with scleroderma -- Dental implants in patients with Sjogren's syndrome -- Dental implants in patients who habitually use smokeless tobacco products -- Dental implants in patients who habitually smoke tobacco -- Dental implants in patients with genetic disorders -- Dental implants in patients with human immunodeficiency virus infection or acquired immune deficiency syndrome.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on August 13, 2018).
Keywords: Dental Implants; Evidence-based dentistry; MEDICAL / Surgery / General; Dental implants; Evidence-based dentistry; Dental Implants; Evidence-Based Dentistry; Risk factors; Electronic books